Analisis Pengendalian Kualitas Susu Domba Bubuk Menggunakan Pareto dan Fishbone Di Indo Natural Farm: Quality Control Analysis of Goat Milk Powder Using Pareto and Fishbone Diagrams at Indo Natural Farm - Agung, Farel (Jurnal Teknologi Agro-Industri, 2025)
This study aims to analyze the quality control of Goat milk powder products at Indo Natural Farm using a Statistical Quality Control (SQC) approach through the application of Pareto and Fishbone diagrams. The research was conducted using a descriptive qualitative approach supported by quantitative data, in which product defect data such as clumping, inappropriate color, insufficient content, and damaged packaging were collected during January–February 2025. The Pareto diagram was used to determine problem priorities based on the frequency of defects, while the Fishbone diagram was applied to identify the root causes of major product defects. The analysis showed that the most dominant defects were clumping powder (28%) and insufficient content (26%), so improvement efforts were focused on these two issues. The main contributing factors included inconsistencies in the drying process, operator errors, raw material quality, and suboptimal control of the production environment. Recommendations for improvement include enhanced operator training, process standardization, and better environmental control. The application of these methods proved effective in minimizing defects and improving the quality of Goat milk powder products at Indo Natural Farm.